South Sulawesi Astra Motor Dealer Marketing Communication Strategy in Building Honda’s Brand Image through Sport Sponsorship - Reda, Moh. Arif; Akbar, Muh.; Fitriana, Fitriana (Journal La Bisecoman, 2023)
The purpose of this research is to determine the marketing communication strategy of the South Sulawesi Astra Motor Dealer in Building the Honda Brand Image in South Sulawesi through the Makassar PSM Club. This research uses descriptive qualitative using Marketing Mix 7 P. The data collection technique used is observation, face-to-face interviews. and documentation. The results of the research show that the Marketing Communication Strategy of the South Sulawesi Astra Motor Dealer in Building Honda’s Brand Image in South Sulawesi through the Makassar PSM Club. The Astra Motor South Sulawesi Marketing Communication Strategy in building Honda’s Brand Image through a partnership with PSM Makassar succeeded in increasing the image and sales of the product. Through a 7P marketing mix approach which includes product, price, place, promotion, people, process and physical evidence, Astra Motor utilizes PSM’s strong support base to create positive associations with the Honda brand.